Factors Predicting Parents’ Readiness to Facilitate Healthy Anxiety Management for Their Children - Inaam Mahmood Talab; Mohammed Baqer Habeeb Abd Ali (Migration Letters, 2023)
Anxiety disorders significantly impact children’s well-being and academic performance. While parents play a crucial role in managing their children’s anxiety, their readiness to facilitate healthy anxiety management remains unclear. This descriptive predictive study aims to identify factors that can predict parents’ readiness to facilitate healthy anxiety management for their children. The participants in this study were 400 parents of children aged 6-13-years who were enrolled in local public schools. The study results reveal that the child’s mean age is 11.37 ± 0.87; more than two-fifth age 12-years (n = 179; 44.75%), followed by those who age 11-years (n = 140; 35.0%), those who age 10-years (n = 49; 12.25%), those who age 13-years (n = 20; 5.0%), and those who age 9-years (n = 12; 3.0%). The regression model demonstrates that the child’s anxiety positively predicts more parents’ readiness to facilitate healthy anxiety management. This finding could be explained as that once the parents realize that their child experiences anxiety that is above the normal limit, this may propel them seek solutions for their child’s condition by facilitating the healthy anxiety management for their children. Parents who recognized the potential benefits and gains of managing their children’s anxiety in a healthy manner were more ready to engage in these behaviors. However, parents who also weighed the potential challenges and drawbacks but still perceived the benefits as outweighing the costs were also more ready to facilitate healthy anxiety management. To promote parents’ readiness to facilitate healthy anxiety management, it is important to highlight the positive aspects (Pros) of this behavior, such as the potential benefits for their children’s well-being for further researchers.